FDA-Approved Hydrogel-Mediated In Situ Sonodynamic and Chemotherapeutic Therapy for Pancreatic Cancer - Jian Wang; Nianhui Yu; Yunpeng Tang; Yingsheng Cheng; Hui Li (Pharmaceuticals)
Background: Albumin-bound paclitaxel (nab-PTX) nanoparticles have been proven effective in treating advanced pancreatic cancer. However, the clinical application of nab-PTX nanoparticles is often associated with suboptimal outcomes and severe side effects due to its non-specific distribution and rapid clearance. This study aims to develop a novel nanoplatform that integrates sonodynamic therapy (SDT) and chemotherapy to enhance treatment efficacy and reduce systemic side effects. Methods: Bovine serum albumin (BSA) was conjugated with chlorin e6 and paclitaxel (PTX) to form stable nanoparticles (NPs). These NPs were then incorporated into a biodegradable poly(lactic-co-glycolic acid)–b-polyethylene glycol–b–poly(lactic-co-glycolic acid) hydrogel for targeted drug delivery. The system’s stability and drug release profile were analyzed, followed by in vitro studies to evaluate cellular uptake and cancer cell killing efficacy. In vivo evaluation was performed using pancreatic cancer xenograft models, with intratumoral injection of the drug-loaded hydrogel. Results: The developed hydrogel system demonstrated enhanced stability and sustained release of PTX. In vitro analyses revealed significant cellular uptake and synergistic cancer cell killing effects through combined SDT and chemotherapy. In vivo studies showed prolonged intratumoral retention of the drug and remarkable inhibition of tumor growth. Conclusions: This novel nanoplatform offers a promising approach for improving pancreatic cancer treatment by enhancing intratumoral drug retention and minimizing systemic side effects. The synergistic effects of SDT and chemotherapy demonstrate the potential of this strategy in achieving better therapeutic outcomes.